The influence of social capital and socio-economic conditions on self-rated health among residents of an economically and health-deprived South African township - Cramm Jane M; Nieboer Anna P (BMC, 2011)
Abstract Background Surprisingly few studies have investigated the interplay of multiple factors affecting self-rated health outcomes and the role of social capital on health in developing countries, a prerequisite to strengthening our understanding of the influence of social and economic conditions on health and the most effective aid. Our study aimed to identify social and economic conditions for health among residents of an economically and health-deprived community. Methods Data were gathered through a survey administered to respondents from 1,020 households in Grahamstown a suburb in the Eastern Cape, South Africa (response rate 97.9%). We investigated the influence of social and economic conditions (education, employment, income, social capital, housing quality and neighborhood quality) on self-rated health. We used ordinal logistic regression analyses to identify the relationship of these conditions and self-rated health. Results Our study found that education and social capital positively correlated with health; unemployment, poor educational level and advanced age negatively correlated. We found no significant correlations between self-rated health and housing quality, neighbourhood quality, income, gender, or marital status. Conclusion We highlight the possible impacts of social capital, employment, and education on health, and suggest that health outcomes may be improved through interventions beyond the health system: creating job opportunities, strengthening social capital, bettering educational systems, and promoting educational access. Policymakers should consider the benefits of such programmes when addressing health outcomes in financially distressed districts.